Lysine Methyltransferase EhPKMT2 Is Involved in the In Vitro Virulence of Entamoeba histolytica - Susana Munguía-Robledo; Esther Orozco; Guillermina García-Rivera; Jeni Bolaños; Jesús Valdés; Elisa Azuara-Licéaga; Mario Alberto Rodríguez (Pathogens, 2023)
Lysine methylation, a posttranslational modification catalyzed by protein lysine methyltransferases (PKMTs), is involved in epigenetics and several signaling pathways, including cell growth, cell migration and stress response, which in turn may participate in virulence of protozoa parasites. Entamoeba histolytica, the etiologic agent of human amebiasis, has four PKMTs (EhPKMT1 to EhPKMT4), but their role in parasite biology is unknown. Here, to obtain insight into the role of EhPKMT2, we analyzed its expression level and localization in trophozoites subjected to heat shock and during phagocytosis, two events that are related to amoeba virulence. Moreover, the effect of EhPKMT2 knockdown on those activities and on cell growth, migration and cytopathic effect was investigated. The results indicate that this enzyme participates in all these cellular events, suggesting that it could be a potential target for development of novel therapeutic strategies against amebiasis.